Corrective movements in response to displacements in visual feedback are more effective during periods of 13-35 Hz oscillatory synchrony in the human corticospinal system. - Androulidakis, A; Doyle, L; Gilbertson, T; Brown, P (2006)
Oscillatory synchronization in the beta (approximately 20 Hz) band is a common feature of human motor control, manifest at cortical and muscular levels during tonic contraction. Here we test the hypothesis that the influence of visual feedback on performance in a positional hold task is increased during bursts of beta-band synchrony in the corticospinal motor system. Healthy subjects were instructed to extend their forefinger while receiving high-gain visual feedback of finger position on a PC screen. Small step displacements of the feedback signal were triggered either by bursts of beta oscillations in scalp electroencephalogram or randomly with respect to cortical beta activity, and the resulting positional corrections expressed as a percentage of the step displacement. Corrective responses to beta and randomly triggered step changes in visual feedback were 41.7+/-4.9 and 31.5+/-6.8%, respectively (P<0.05). A marked increase in the coherence in the beta band was also found between muscle activity and cortical activity during the beta-triggered condition. The results suggest that phasic elevations of beta activity in the corticospinal motor system are associated with an increase in the gain of the motor response to visual feedback during a tonic hold task. Beta activity may index a motor state in which processing relevant to the control of positional hold tasks is promoted, with behavioural consequences.